Organic Selenium Reaches the Central Nervous System and Downmodulates Local Inflammation: A Complementary Therapy for Multiple Sclerosis? - Toledo, Juliana Helena dos Santos de; Fraga-Silva, Thais Fernanda de Campos; Borim, Patrícia Aparecida; de Oliveira, Larissa Ragozo Cardoso; Oliveira, Evelyn da Silva; Périco, Larissa Lucena; Hiruma-Lima, Clélia Akiko; de Souza, Adriana Aparecida Lopes; de Oliveira, Carlos Alberto Ferreira; Padilha, Pedro de Magalhães; Pinatto-Botelho, Marcos Felipe; dos Santos, Alcindo Aparecido; et al. (Frontiers in Immunology, 2020)
Multiple sclerosis (MS) is an inflammatory and demyelinating disease of the central nervous system (CNS). The persistent inflammation observed in the CNS is being related to local oxidative stress and inflammasome activation, both implicated in demyelination and axonal damage. Since the development of new therapeutic procedures remains necessary, we evaluated the efficacy of an immunomodulatory and antioxidant product to control the development of experimental autoimmune encephalomyelitis (EAE) which is an animal model to study MS. The beta-selenium-lactic acid derivative (LAD-βSe) is a source of organic selenium (Se) that is under development by a LabSSeTe (USP/Brazil) and Biorigin Company. This product was tested in three protocols: a prophylactic-therapeutic one, in which LAD-βSe daily oral treatment started 14 days before EAE induction, and two other therapeutics started 1 or 7 days after disease induction. The two therapeutic procedures, which were investigated more intensively, indicated that protection was associated to Se accumulation in the CNS. Protection was concomitant to lower local cellular infiltration, impaired activation status of macrophages/microglia, less NLRP3 inflammasome activation and lower levels of other inflammatory parameters at the CNS. In mesenteric lymph nodes LAD-βSe determined a tolerogenic profile in dendritic cells which could mechanistically contribute to protection. Liver and renal function indicators revealed that protection was not associated to dysfunction of these organs. A model of neurodegeneration triggered by LPS was used to sustain the hypothesis that LAD-βSe was able to act locally at the target organ. The results observed in this model confirmed a higher Se concentration and downmodulation of pro-inflammatory parameters at the CNS. Remarkably, LAD-βSe also therapeutically controlled EAE development in SJL/J mice which is a relapsing-remitting MS model. This study indicates that LAD-βSe, and possibly other derivatives containing Se and able to reach the CNS have the potential to be employed as an adjunct therapy for distinct clinical forms of MS.